Delay in Presentation of Developmental Dysplasia of the Hip (DDH): Average Age at Diagnosis vs Functional and Structural Outcomes - Mobushir, Muhammad; Zafar, Muhammad Hassan; Ur Rehman, Sheikh Abir; Waleed, Usman; Bukhari, Maira; Munir, Wasay; Rahman, Obaid Ur (Biological and Clinical Sciences Research Journal, 2025)
Developmental Dysplasia of the Hip (DDH) represents a spectrum of hip abnormalities that, if undiagnosed or diagnosed late, can result in long-term structural deformities and functional disability. Early detection is critical for optimizing outcomes, but in many developing regions, including Pakistan, delayed presentation remains common. This study aimed to assess the average age at diagnosis of DDH and to evaluate its impact on functional and structural outcomes. Methods: This observational cross-sectional study was conducted at the Department of Paediatric Orthopaedics, Benazir Bhutto Hospital, Rawalpindi, Pakistan, from June 2024 to July 2025. Eighty patients aged 6 months to 4 years diagnosed with unilateral or bilateral DDH were included through non-probability consecutive sampling. Clinical evaluation included gait analysis and range of motion, while radiographic assessment utilized the Tönnis classification for dislocation severity and Severin grading for postoperative radiological outcomes. Functional outcomes were assessed using the McKay Clinical Criteria. Data were analyzed using SPSS version 26.0, with p < 0.05 considered statistically significant. Results: The mean age at Diagnosis was 24.6 ± 8.3 months. Females predominated (77.5%) with a left-side predominance (46.3%). A total of 67.5% of patients presented after 12 months of age. Functional outcomes (McKay score) were significantly better in early-diagnosed cases (<12 months), with 76.9% achieving excellent-to-good outcomes compared with 38.9% in late presenters (p < 0.05). Structural results were also superior among early presenters, with 69.2% achieving Severin Grade I–II compared with 29.6% in the delayed group (p < 0.01). Late diagnosis was associated with greater dislocation severity: 63.0% of late presenters had Tönnis Grade III–IV dislocations, compared with 26.9% of early presenters (p < 0.01). Conclusion: Delayed diagnosis of DDH is strongly associated with increased structural deformity and poorer functional outcomes. Early detection—ideally before 12 months of age—significantly enhances prognosis. Implementing nationwide neonatal screening programs and raising parental awareness can reduce diagnostic delays and improve long-term musculoskeletal health outcomes in the Pakistani population.